2018
DOI: 10.3389/fchem.2018.00573
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Catalytic Acetalization of Bio-renewable Glycerol to Fuel Additives

Abstract: The last 20 years have seen an unprecedented breakthrough in the biodiesel industry worldwide leads to abundance of glycerol. Therefore, the economic utilization of glycerol to various value-added chemicals is vital for the sustainability of the biodiesel industry. One of the promising processes is acetalization of glycerol to acetals and ketals for applications as fuel additives. These products could be obtained by acid-catalyzed reaction of glycerol with aldehydes and ketones. Application of different suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 145 publications
(132 reference statements)
2
78
0
Order By: Relevance
“…From the intersection of the natural logarithm of the reaction rate with 1 / T (K), the apparent activation energy was calculated (Figure 7). The value obtained (57.1 kJ mol -1 ) agrees with the value obtained by Talebian-Kiakalaieh and Amin, 33 who performed the glycerol dehydration using HSiW-γ-Al 2 O 3 supported ); TOF glycerol (TAS) and TOF glycerol (BAS): TOF glycerol calculated considering TAS and BAS, respectively; Al: alumina; 10MoAl, 10VAl, 10Mo10VAl: catalysts containing molybdenum, vanadium, and molybdenumvanadium, respectively. in ZrO 2 and measured a global activation energy of 46.9 kJ mol -1 .…”
Section: Catalytic Activitysupporting
confidence: 87%
See 1 more Smart Citation
“…From the intersection of the natural logarithm of the reaction rate with 1 / T (K), the apparent activation energy was calculated (Figure 7). The value obtained (57.1 kJ mol -1 ) agrees with the value obtained by Talebian-Kiakalaieh and Amin, 33 who performed the glycerol dehydration using HSiW-γ-Al 2 O 3 supported ); TOF glycerol (TAS) and TOF glycerol (BAS): TOF glycerol calculated considering TAS and BAS, respectively; Al: alumina; 10MoAl, 10VAl, 10Mo10VAl: catalysts containing molybdenum, vanadium, and molybdenumvanadium, respectively. in ZrO 2 and measured a global activation energy of 46.9 kJ mol -1 .…”
Section: Catalytic Activitysupporting
confidence: 87%
“…With exception of bimetallic material, it was observed that the TOF increases as surface area increases, according to the greater activity expected for materials with greater area available to convert glycerol. 33 When analyzing only the effect of Brønsted acid sites in the TOF, the cooperative effect between the Brønsted and Lewis sites in the acrolein formation is confirmed, since 10MoAl, even with the smallest quantity of Brønsted acid sites between supported materials, has the highest selectivity to acrolein, indicating that not only the Brønsted sites act in the acrolein formation.…”
Section: Catalytic Activitymentioning
confidence: 86%
“…Glycerol ketals are interesting as fuel additives (oxygenates) [20][21][22], fuel antioxidants [23] and as reactive oxygen species (ROS) scavengers able to act in-vitro and in-vivo [24]. Solketal, in particular, is known to reduce gum formation and particulate emissions, enhance fuel flow in cold conditions, improve stability towards oxidation, and boost octane number when it is added to gasoline, which contributes to reducing the environmental impact (the LD50 for fish is higher than 3100 ppm for solketal, while for MTBE it is 1000 ppm) [25]. [19]).…”
Section: Introductionmentioning
confidence: 99%
“…Based on DRIFTS results, we propose a possible reaction mechanism of Ni 1.5 Rh 1.5 /γ‐Al 2 O 3 ‐catalyzed acetalization for FFR and two ethanol molecules containing active α‐hydrogen atoms, as shown in Figure . First, the nickel center of Ni 1.5 Rh 1.5 /γ‐Al 2 O 3 polarizes the C=O bond of FFR; thus, the coordination of the oxygen atom of carbonyl to Ni(0) center forming Ni δ+ ‐(η 1 ‐O,C‐FFR) species can enhance the carbonyl's electrophilicity step in this case . Simultaneously, rhodium center of Ni 1.5 Rh 1.5 /γ‐Al 2 O 3 reacts with the alcohol (Step 1, Figure ), promoting a hydride transfer to the oxygen atom of the furfural carbonyl and forming a rhodium‐ethoxide intermediate (Step 2, Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…First, the nickel center of Ni 1.5 Rh 1.5 / γ-Al 2 O 3 polarizes the C=O bond of FFR; thus, the coordination of the oxygen atom of carbonyl to Ni(0) center forming Ni δ + -(η 1 -O,C-FFR) species can enhance the carbonyl's electrophilicity step in this case. [51] Simultaneously, rhodium center of Ni 1.5 Rh 1.5 / γ-Al 2 O 3 reacts with the alcohol (Step 1, Figure 6), promoting a hydride transfer to the oxygen atom of the furfural carbonyl and forming a rhodium-ethoxide intermediate (Step 2, Figure 6). The protonated carbonyl group undergoes the nucleophilic attack of O atom of the ethanol [52] and subsequently, a second molecule of ethanol is added to the rhodium center (Step 3, Figure 6).…”
Section: Physical Chemistry Properties Of the Catalysts Surfacementioning
confidence: 99%